Answer:
Please check the explanation.
Explanation:
Given the geometric sequence
a – 2, a, a + 4
- We know that the common ratio 'r' of a geometric sequence can be obtained by dividing the successor term by the previous term.
- Also, we know that the common ratio 'r' of a geometric sequence is the same i.e. remain constant.
so the expression to find the common ratio 'r' of the geometric sequence will be:
⇒
so the ratio becomes
Hence, the common ratio 'r' will be:
VERIFICATION
so the sequence becomes
a – 2, a, a + 4
(4) - 2, 4, (4)+4 ∵ a=4
2, 4, 8
From the sequence it is clear that
4/2=8/4 ⇒ r
2=2 ⇒ r
Hence, the common ration 'r=2' is the same.
Therefore, the common ratio 'r' will be: